Aging : a beautiful journey - Khairuddin Yusof (Shah Alam : UiTM Press, 2012)
This book is a personal journey into aging covering almost a life time of physical activities and exercises. Professor Emeritus Dato Dr Khairuddin Yusof had traced his interest in physical activities and sports covering a period of 66 years. He described his triumph and personel tragedies of life events, his failure and successes of overcome adversities. He had provided useful information's, impression and perceptions in overcoming aging. His academic experience had given him a deep understanding in exercise; what works for him and what doesn't. He has provided useful template for others who wanted to emulate his journey into aging.
Includes bibliographical references (p. [175]-176) and index.
Keywords: Aging; Older people -- Health and hygiene; Exercise for older people